Land-use function evolution and eco-environmental effects in the tarim river basin from the perspective of production–living–ecological space - Wang, Yang; Wang, Yin; Xia, Tingting; Li, Yang; Li, Zhi (Frontiers in Environmental Science, 2022)
The identification of land type multi-functionality is a basic tool for the organization, coordination, and configuration of basin land, and provides a key criterion for determining the combination of land-use functions and the status quo of the ecological environment in the basin. However, a feasible identification method system for this purpose has not yet been established. Therefore, in this study, we construct a production–living–ecological space (PLES) classification system from the comprehensive perspective of land-use type and ecological environment. Based on remote sensing of PLES and statistical land-use status data for 2000, 2005, 2010, 2015, and 2020, we analyze the evolutionary characteristics of land-use function using the transfer matrix and center of gravity transfer methods. These are combined with the eco-environmental quality index to reveal the driving factors of eco-environmental quality spatial differentiation using the geographic detector model. The results indicate that the overall ecological environment quality index of the Tarim River Basin presents a downward trend, with a spatial differentiation pattern of high in the northwest and low in the southeast. Over the past 20 years, the ecological environment quality index has dropped by 0.852. The structural evolution and regional differentiation of PLES areas are remarkable, all of which expanded over the study period (except for the key ecological land). The center of gravity of production land presented the most obvious migration, with a total migration of 10,601.76 m to the northeast. Eco-environmental effects are found to be mainly driven by socio-economic factors, of which population density growth is the most important. The implementation of some ecological restoration projects has played a role in slowing down the degradation trend of the ecological environment quality in the Tarim River Basin; however, due to population increases and socio-economic development, the ecological environment degradation has overall been exacerbated.